Media and youth and the phenomenon of violence in the stadiums of Algerian football - رداوي فريد (sports creativity, 2025)
The context in this research is to study the violence in stadiums nearly spread in arab and non arab societies as well. We try to study and to describe the violence phenomena by both sides psychological and sociological. We study also the role of the telecommunication means in feeding the violence, because there is a link between the media and the youth in the violence progress in Algeria. We work on studying the phenomena and try to find solutions particularly in Algerian stadiums. The importance of this study is in looking for a solution to a mean problem that still represents a real danger on Algerian society. Dangers in Algerian stadiums extend to children and young classes. So it is very important to find mechanisms and procedures to make an end to the violence phenomena in football stadiums and to determine the role of the media means in that. It is an energy itself, an energy that must be guided and oriented. Without orientation, the young will not find a single space where they explode their energies, so they use them violently in stadiums. They also use the media to spread their ideas about violence within these sportive spaces.